2000
DOI: 10.1029/1999jd901018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of natural hydrocarbons on ozone formation in an isolated power plant plume

Abstract: Abstract. On 4 days during the 1995 Southern Oxidant Study (SOS), air samples were taken in the plume of the Cumberland Power Plant in Tennessee using an instrumented helicopter. On these days a notable difference in excess ozone in the plumes was observed. Excess ozone varied from 20 ppb on July 7, 1995, up to 55 ppb on July 16. While the total amount of non-methane VOC was quite similar, significant dift•rences xvere observed in the levels of reactive hydrocarbons, mostly isoprene. This study exainines the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…(3) The sensitivity analyses show that while the modeled chemical OPE appears to be relatively insensitive to the dilution rate for the present episode, it responds nonlinearly to changes in NO x and anthropogenic VOC emissions. It decreases at high NO x , increases at high VOC and vice versa, which are consistent with previous studies [ Liu et al , 1987; Lin et al , 1988; Luria et al , 2000; Daum et al , 2000; Ryerson et al , 1998, 2001]. The corresponding downwind O 3 concentrations responded in a nonlinear fashion as well.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(3) The sensitivity analyses show that while the modeled chemical OPE appears to be relatively insensitive to the dilution rate for the present episode, it responds nonlinearly to changes in NO x and anthropogenic VOC emissions. It decreases at high NO x , increases at high VOC and vice versa, which are consistent with previous studies [ Liu et al , 1987; Lin et al , 1988; Luria et al , 2000; Daum et al , 2000; Ryerson et al , 1998, 2001]. The corresponding downwind O 3 concentrations responded in a nonlinear fashion as well.…”
Section: Discussionsupporting
confidence: 91%
“…Thus each point on the lines in this figure represents the chemical OPE predicted at the end point C 3 (indicated in Figure 4) for the corresponding scaling factor value applied to the base case emissions and initial concentrations as mentioned earlier. The figure shows that OPE decreases at high NO x concentrations as was predicted by Liu et al [1987] and observed by Ryerson et al [1998, 2001], and increases at high VOC concentrations as observed by Luria et al [2000] and Ryerson et al [2001]. However, it should be also noted that part of the increase of OPE at low is due to PAN decomposition to give back NO 2 .…”
Section: Sensitivity Analysissupporting
confidence: 64%
“…Isoprene plays an important role in O 3 formation in rural areas [ Trainer et al , 1987], cities [ Chameides et al , 1988], and power plant plumes [ Luria et al , 2000; Ryerson et al , 2001]. It is very reactive (k OH = 9.7 × 10 −11 cm −3 s −1 ) so that even levels below ppb can dominate the overall OH‐VOC reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Isoprene can play an important role in O 3 formation in rural areas , for cities (Chameides et al, 1988), and for power plant plumes (Luria et al, 2000;Ryerson et al, 2001). It is very reactive (kOH = 10.0 ± 1.2 × 10 −11 cm 3 molecule −1 s −1 at 294 K; Karl et al, 2006) and thus even sub-ppb levels can dominate the overall OH-VOC reactivity.…”
Section: Isoprene Oxidation Pathways: Change Frommentioning
confidence: 99%